The transmission mechanism of monetary policy via bank’ balance sheet: an empirical study of dual banking system in Pakistan - Kabir, Anis; Abdul Rehman Shah, Syed Muhammad; Hassan, M. Kabir; Akmal, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study empirically analyzes the MPTM through bank’ balance sheet in Pakistan for the period of 2008-2018. The data set consists of 22 conventional banks and 18 Islamic banks (5 full-fledged and 13 Islamic windows of conventional banks) of Pakistan. The study employs the robust two-step system-Generalized Method of Moments is applied for estimation and confirms the presence of balance sheet channel in Pakistan. The study also finds that responses of Islamic banking operations to monetary policy shocks are not different from their conventional peers because both banking systems use Karachi Interbank offered rate (KIBOR) as a benchmark for their products. The results also highlight the sensitivity of banking operations (conventional vs Islamic) to monetary policy shocks are quite different, mainly due to the difference in their nature of contracts. This study is equally beneficial for academicians and practitioners to consider the nature of both banking systems in same economy. Our findings indicate that, policy makers need to consider the nature of both banking system (conventional vs Islamic) to maintain deposits and credit supply in an economy.